A The Impact of Loose Parts Collage Activities in Building Environmental Care Character at TK Harapan Ibu, Tanah Datar - Intan Sri Intan Wahyuni (Tajdid Al-Athfal, 2024)
This research is motivated by the fact that there are still children who do not care about the environment, there are also children who throw garbage out of place and there are also those who scribble on the walls, this happens because of the lack of planting the character of environmental care in children. This study aims to determine whether collage activities with loose part materials have an effect on children's environmental care character.at TK Harapan Ibu Sikaladi This study uses a type of quantitative research experimental method with a pre experimental design type one group pretest posttest design. The population in this study were children at TK Harapan Ibu Sikaladi totaling 29 children consisting of 2 classes, namely B1 totaling 14 children and B2 totaling 15 children. The type of sample used is random sampling technique. The sample in this study was class B2 with a total of 15 people. The instrument used is a checklist instrument with data collection techniques, namely observation and documentation. Based on the results of the research and data analysis that the researchers have carried out on the effect of collage activities with loose part materials on the environmental care character of children aged 5-6 years at TK Harapan Ibu Jorong Sikaladi Nagari Pariangan Kecamatan Pariangan Kabupaten Tanah Datar, then obtained the pre-test value of 20.53 and the posttest value of 28.93 calculated the df, df = N - 1 = 14, comparing the amount of t that will be obtained with the calculation of t = 15.97 and the amount of t listed at a significant level of 5%, namely 1.76131. so it can be known that to is greater than t, namely 15.97> 1.76131. So the alternative hypothesis is accepted, because collage activities with loose part materials affect the character of environmental care for children aged 5-6 years at TK Harapan Ibu Sikaladi. Then the Ha hypothesis is accepted and the Ho hypothesis is rejected. So it can be concluded that collage activities with loose part materials can affect the character of caring for the environment of children aged 5-6 years at TK Harapan Ibu Jorong Sikaladi Nagari Pariangan Kecamatan Pariangan Kabupaten Tanah Datar